Ambulance nurses' experiences of deciding a patient does not require ambulance care - Tess Backman; Päivi Juuso; Ronja Borg; Åsa Engström (Wiley, 2019)
Abstract Aim To describe ambulance nurses' experience of deciding a patient does not require ambulance care. Design An inductive, empirical study with a qualitative approach. Methods Data collection was conducted through semi‐structured interviews, and collected data were analysed with qualitative manifest content analysis. Data were collected during the spring 2017, and eight ambulance nurses participated. Results The findings are presented in one main category, which is "Not very ill but a difficult decision" with totally three subcategories. The ambulance nurse's experience of making the assessment when the patient has no need for ambulance care is like walking the balance of slack line. This means that the assessment can be both easy and very difficult but something that definitely requires experience, knowledge and dedication.